Enhancing students’ critical thinking skills in reading class using the directed reading thinking activity (DRTA) teaching strategy - Rizka Jannatul Muthoharoh; Hartono Hartono (EduLite: Journal of English Education, Literature and Culture, 2022)
This research aims to analyze the effectiveness of the DRTA strategy in enhancing students’ critical thinking skills in English reading. It applied a pre-test and post-test quasi-experimental design. The samples of this study were 37 students of the XI-MIPA of Madrasah Aliyah Miftahul Huda Tayu. The instrument for collecting data was a test. It was six questions of analytical exposition text presented in an essay-type form. A t-test was used to analyze the mean score difference between the control and experiment groups. After treatment, there was an improvement in students’ critical thinking skills. The value of t0 is 2.274 and ttable is 2.030. The result of the computation was 2.274 > 2.030, while the sig. (2-tailed) was 0.029 < 0.05. There was a significant difference in the students’ critical thinking skills between those who were taught reading using the DRTA strategy and those who were not. The DRTA strategy effectively enhanced the student’s critical thinking skills in reading.